Fungus Pichia kudriavzevii XTY1 and heterotrophic nitrifying bacterium Enterobacter asburiae GS2 cannot efficiently transform organic nitrogen via hydroxylamine and nitrite - Xu, Tianyue; Song, Simeng; Ren, Baihui; Li, Jiahuan; Yang, Jiyun; Bai, Long; Piao, Zhongyun (Frontiers in Microbiology, 2022)
Heterotrophic nitrification is a process of organic nitrogen degradation completed by the participation of heterotrophic nitrifying microorganisms, which can accelerate the nitrogen transformation process. However, the current research mainly focuses on heterotrophic nitrifying bacteria and their ammonium degradation capacity, and there is little accumulation of research on fungi, the main force of heterotrophic nitrification, and their capacity to transform organic nitrogen. In this study, novel heterotrophic nitrifying fungus (XTY1) and bacterium (GS2) were screened and isolated from upland soil, and the strains were identified and registered through Gene Bank comparison. After 24 h single nitrogen source test and 15N labeling test, we compared and preliminarily determined the heterotrophic nitrification capacity and pathways of the two strains. The results showed that XTY1 and GS2 had different transformation capacities to different nitrogen substrates and could efficiently transform organic nitrogen, but the transformation capacity of XTY1 to ammonium was much lower than that of GS2. The two strains did not pass NH2OH and NO2- during the heterotrophic nitrification of organic nitrogen, and mainly generated intracellular nitrogen and low N2O. Other novel organic nitrogen metabolism pathways may be exist, but they remain to be further validated.